WOMEN’S PETITIONS SENT THROUGH LETTERS: EXPECTATIONS ABOUT THE REACH OF SALESIAN ASSISTANCE. (ARGENTINA,1900-1930) - Bracamonte, Lucía (2025)
The salesian congregation proposed attending the social matter of childhood, considered endangered and risky to the social order. In this context there were women who engaged relationships with salesians to receive aid and collaborate as cooperators. This article will examine the requests for asistance in personal, familial and friendly matters that were made by women through letters in the first three decades of the 20th century. The objective is to reflect on two dimensions: the expectations they had about the reach of salesian aid and, secondarily, the reception their claims had. It’s claimed that those requests were transversal to the social classes and exceeded the places were the congregation’s houses and cooperatives’s commissions. Moreso, it sustains that these women intended to extend the predetermined limits of salesian aid that revolved around the applications for admission of children and young people to schools, support in devotional matters and support for community religious and educational endeavors. In fact, they petitioned to obtain favours, social, economical and political intermediation and help in economic matters for themselves and people on their most immediate circles.